Effects of Composition of Iron-Cross-Linked Alginate Hydrogels for Cultivation of Human Dermal Fibroblasts. (13th December 2012) - Machida-Sano, Ikuko; Ogawa, Sakito; Ueda, Hiroyuki; Kimura, Yoshitaka; Satoh, Nao; Namiki, Hideo
Abstract : We investigated the suitability of ferric-ion-cross-linked alginates (Fe-alginate) with various proportions of L-guluronic acid (G) and D-mannuronic acid (M) residues as a culture substrate for human dermal fibroblasts. High-G and high-M Fe-alginate gels showed comparable efficacy in promoting initial cell adhesion and similar protein adsorption capacities, but superior cell proliferation was observed on high-G than on high-M Fe-alginate as culture time progressed. During immersion in culture medium, high-G Fe-alginate showed little change in gel properties in terms of swelling and polymer content, but the properties of high-M Fe-alginate gel were altered due to loss of ion cross-linking. However, the degree of cell proliferation on high-M Fe-alginate gel was improved after it had been stabilized by immersion in culture medium until no further changes occurred. These results suggest that the mode of cross-linkage between ferric ions and alginate differs depending on alginate composition and that the major factor giving rise to differences in cell growth on the two types of Fe-alginate films is gel stability during culture, rather than swelling of the original gel, polymer content, or protein adsorption ability. Our findings may be useful for extending the application of Fe-alginate to diverse biomedical fields.